Adjuvant rituximab, a potential treatment for the young patient with Graves' hyperthyroidism (RiGD): study protocol for a single-arm, single-stage, phase II trial. Issue 1 (21st January 2019) - Cole, Michael; Hynes, Ann Marie; Howel, Denise; Hall, Lesley; Abinun, Mario; Allahabadia, Amit; Barrett, Timothy; Boelaert, Kristien; Drake, Amanda J; Dimitri, Paul; Kirk, Jeremy; Zammitt, Nicola; et al.
Abstract : Introduction: Graves' disease (Graves' hyperthyroidism) is a challenging condition for the young person and their family. The excess thyroid hormone generated by autoimmune stimulation of the thyroid stimulating hormone receptor on the thyroid gland can have a profound impact on well-being. Managing the young person with Graves' hyperthyroidism is more difficult than in older people because the side effects of conventional treatment are more significant in this age group and because the disease tends not to resolve spontaneously in the short to medium term. New immunomodulatory agents are available and the anti-B cell monoclonal antibody rituximab is of particular interest because it targets cells that manufacture the antibodies that stimulate the thyroid gland in Graves'. Methods and analysis: The trial aims to establish whether the combination of a single dose of rituximab (500 mg) and a 12-month course of antithyroid drug (usually carbimazole) can result in a meaningful increase in the proportion of patients in remission at 2 years, the primary endpoint. A single-stage, phase II A'Hern design is used. 27 patients aged 12–20 years with newly presenting Graves' hyperthyroidism will be recruited. Markers of immune function, including lymphocyte numbers and antibody levels (total and specific), will be collected regularly throughout the trial. Discussion: The trial will determine whether the immunomodulatory medication, rituximab, will facilitate remission above and beyond that observed with antithyroid drug alone. A meaningful increase in the expected proportion of young patients entering remission when managed according to the trial protocol will justify consideration of a phase III trial. Ethics and dissemination The trial has received a favourable ethical opinion (North East - Tyne and Wear South Research Ethics Committee, reference 16/NE/0253, EudraCT number 2016-000209-35). The results of this trial will be distributed at international endocrine meetings, in the peer-reviewed literature and via patient support groups. Trial registration number: ISRCTN20381716 .